2013
DOI: 10.1021/am402305u
|View full text |Cite
|
Sign up to set email alerts
|

Ce(III) Doped Zr-Based MOFs as Excellent NO2Adsorbents at Ambient Conditions

Abstract: New hybrid cerium modified zirconium based metal-organic frameworks (MOFs) were synthesized. The as-received materials were evaluated as adsorbents of NO2 in either moist or dry conditions. The surface of the initial and exhausted samples was characterized using XRD, SEM-EDX, nitrogen adsorption, thermal analysis, and FTIR. It was found that the addition of Ce(+3) slightly affects the growth of the framework and introduces new features to Zr-MOF. The shapes of the octahedral crystals are changed, and they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(95 citation statements)
references
References 58 publications
5
85
0
Order By: Relevance
“…8,9 However, the in situ doped MnCeMOF showed a very low catalytic ability of below 20% in the SCR of NO (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 However, the in situ doped MnCeMOF showed a very low catalytic ability of below 20% in the SCR of NO (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…MnCeMOF exhibited a higher BET surface area and larger pore volume than the undoped MOF. Based on the Ebrahim's point, 8 Mn-Ce doping may inhibit the complete growth of the MOF and lead to crystal defects, which result in an increase in the pore volume. Moreover, during the synthesis of MnCeMOF, Mn/Ce may become sites of crystal growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various modulators have been used to tune the size and morphology of UiO-66 crystals. The modulation mechanism of hydrofluoric acid as well as the changes in structure and 5 properties of UiO-66 crystals caused by the introduction of fluorine was also studied. They also synthesized a Zr-based MOF using fumarate (fum) dianions as linkers and formic acid as a modulator.…”
Section: Introductionmentioning
confidence: 99%
“…From the FTIR spectra ( Figure 1a), it can be observed that, for the bdc ligand, the stretching vibrations of C═O and symmetric-asymmetric stretching of O-C-O band in the carboxylic acid appeared at 1674 and 1418 cm À1 , respectively, while the peaks that appeared at 892, 724, and 504 cm À1 were assigned to the C-H plane bending vibration of benzene ring. [34][35][36] For the dpNDI ligand, the weak peaks that appeared at 3383 and 3058 cm À1 were represented to N-H stretching bands; the bands detected at 1674 and 1568 cm À1 were also assigned to the stretching vibrations of C═O in the amide present in dpNDI. [37] For the [Zn 2 (bdc) 2 (dpNDI)] n frame works, the N-H stretching band appeared at 3191 cm À1 and shows redshift for about 133 cm À1 , which was compared with pure dpNDI ligand; this may be caused from the conformation of larger conjugated system between bdc and dpNDI ligand.…”
Section: Chemical Composition and Morphology Of [Zn 2 (Bdc) 2 (Dpndi)mentioning
confidence: 99%